Coverage of the Holodomor of 1932-1933 in Ukraine in the English-Speaking Media as an Antidote to the Soviet Disinformation Policy - Dyazhur, Denys (Ukrainian Peasant, 2024)
The purpose of the article. The author of the article aims to investigate the methods used by the Soviet government, particularly through contemporary media, to suppress information about the Holodomor of 1932—1933 in Ukraine. Additionally, the article seeks to illuminate how English-language mass media countered the spread of Soviet disinformation regarding the Holodomor in Ukraine. The scientific novelty. The previous issue of reflecting objective facts about the Holodomor of 1932—1933 in Ukraine in English-language media, as well as the mechanisms of Soviet propaganda to suppress information about the Holodomor, has been explored in the works of A. Kozytskyi, V. Gudz, A. Mikheiev, and other researchers. Most studies by these scholars focus either on describing the events or on Soviet disinformation policies in general. Our study focuses on specific methods through which English-language media countered Soviet disinformation, analyzing specific articles, reports, and testimonies of journalists, while also considering specific examples of disinformation spread in Soviet media. Conclusions. Seeking to control information about the famine in Ukraine, the Soviet government prevented foreign journalists from freely accessing the affected areas to conceal the scale of the famine and prevent international outcry. Soviet media reacted to reports in foreign mass media by attempting to refute information about the famine in the USSR and portray it as an anti-Soviet smear campaign to discredit Western sources. Despite active disinformation efforts by the Soviet government, truthful accounts of the Holodomor of 1932—1933 in Ukraine began appearing in the foreign press due to witnesses, journalists, diplomats, politicians, and public figures from Western countries. Newspapers such as «The Guardian», «The New York Times», «New York Herald Tribune», «Daily Telegraph», and others regularly reported on the unprecedented famine in Ukraine. Publications by G. Jones and M. Muggeridge sustained international interest in the Ukrainian situation and kept the issue of famine in the forefront of global public opinion, making it more difficult for the Soviet authorities to conceal the truth.